Pengaruh Pola Asuh Orang Tua terhadap Perkembangan Kemandirian Anak Usia Dini - mulyati, Cicin; Supriyadi, Supriyadi; Kurniawaty, Lia (INTELEKTIUM, 2025)
This study aims to determine the influence of parenting styles on early childhood independence and the extent of this influence. The research method used in this study is quantitative research with a survey approach. The population of this study was 110 parents of students at SPS Al Firdaus and other institutions around Sawit Village, Darangdan District. The sampling technique used was purposive sampling, resulting in a sample size of 25 people. Data collection used a questionnaire distributed via a Google Form link. The questionnaire used to determine the influence of parenting styles on early childhood independence was a closed-ended questionnaire. The data analysis used in the hypothesis testing was simple linear analysis. The results of the study show that: (1) There is an influence of the parenting pattern variable (X) on the independence of early childhood children (Y) with a Sig. value of 0.000 < 0.05. (2) The positive constant value obtained of 133.925 indicates that parenting patterns (X) have a positive effect on early childhood independence (Y) and the magnitude of the influence of the parenting pattern variable (X) on the early childhood independence variable (Y) is 9.8%, while the remaining 90.2% is influenced by other factors.